128: The Burden of Prenatal Exposure to Alcohol: 2013 Revised Measurement of Cost. Issue 6 (1st June 2014) - Stade, BC; Watson, W; Campbell, D; Bonifacio, J; Hignell, A; Koren, G; Sgro, M
Abstract: BACKGROUND: In Canada the incidence of Fetal Alcohol Spectrum Disorder (FASD) is estimated to be one in 100 live births. FASD is the leading cause of developmental and cognitive disabilities in Canada. In 2007, we examined the cost of FASD in Canada. In that study we did not include prospective data of the cost of diagnosis, the cost of integrating homeless youth into the community, and the cost beyond 53 years of age. OBJECTIVES: To calculate a revised estimate of direct and indirect costs associated with FASD at the patient level. DESIGN/METHODS: Cross-sectional study design was used. Three-hundred and five (305) participants completed the study tool. Participants included caregivers of children, youth and adults, with FASD, from day of birth to 65 years, living in urban and rural communities throughout Canada. Participants completed the Health Services Utilization Inventory (HSUI). Key cost components were elicited: direct costs: medical, education, social services, out-of-pocket costs; and indirect costs: productivity losses. Total average costs per individual with FASD were calculated by summing the costs for each in each cost component, and dividing by the sample size. Costs were extrapolated to one year. A stepwise multiple regression analysis was used to identify significant determinants of costs and to calculate the adjusted annual costs associated with FASD. RESULTS: Total adjusted annual costs associated with FASD at the individual level was 32, 840 (95% CI 26, 452 to 40, 092), compared to 21, 642 (95% CI 19, 842 to 24, 041) in the last study. Severity of the individual's condition, intellectual level, age, and relationship of the individual to the caregiver (biological, adoptive, foster) were significant determinants of costs (P<0.001). Cost of FASD annually to Canada of those from day of birth to 65 years old, was 6.8 billion (95% CI 5.2 billion to 7.4 billion). CONCLUSIONS: Study results demonstrated the cost burden of FASD in Canada was profound. Inclusion of the cost of diagnosis, adults beyond the age of 53 years, and the costs of integrating homeless youth into the community provided a more accurate estimate of the costs of FASD. Implications for practice, policy, and research are discussed.